Qualidade do sono e o potencial cognitivo P300 em pessoas idosas: um estudo transversal - Julião, Elynaide Cinthia da Silva (Universidade Federal de São Carlos, 2024)
Introduction: The P300 is a long-latency evoked potential that occurs approximately 300 milliseconds after the onset of a relevant stimulus. The P300 can be assessed by measuring the latency and amplitude of the P3 wave, related to information processing time and level of attention, respectively. Objective: To verify the correlation between sleep quality and the latency and amplitude of the P3 wave in elderly people. Methodology: Quantitative observational cross-sectional study carried out with 28 elderly people, without cognitive changes or hearing loss. Sociodemographic data, latency and amplitude of the P300 test and the mini-sleep questionnaire were used, which assumed the role of dependent variable, defining two study groups: with good sleep and with altered sleep. Comparative statistics were applied between the groups using the Mann-Whitney test and correction using the Spearman test, with a significance of 5%. Results: The results indicated that the group with altered sleep quality had a lower P3 wave amplitude in the Cz and Pz channels and that the greater the sleep change, the lower the P3 wave amplitude in the Fz channel (R=-0.46, p=0.02). There was no significant difference in P300 wave latency between groups. Discussion: P300 amplitude was sensitive to changes in sleep quality, reflecting deficits in attention and cognitive processing, while latency remained unchanged. Conclusion: There is a correlation between P300 wave amplitude and sleep quality in elderly people, suggesting that poor sleep quality negatively impacts cognitive performance.
Sleep quality and cognitive potential P300 in elderly individuals: a cross-sectional study
Keywords: Idoso; Cognição; Potenciais evocados, P300; Qualidade do sono; Aged; Cognition; Event-related potentials, P300; Sleep quality; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::FONOAUDIOLOGIA